2018
DOI: 10.3389/fpsyt.2018.00102
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-Like Effects of Acupuncture-Insights From DNA Methylation and Histone Modifications of Brain-Derived Neurotrophic Factor

Abstract: Sensitive and stable biomarkers that facilitate depression detection and monitor the antidepressant efficiency are currently unavailable. Thus, the objective is to investigate the potential of DNA methylation and histone modifications of brain-derived neurotrophic factor (BDNF) in monitoring severity and antidepressive effects of acupuncture. The depression rat model was imitated by social isolation and chronic unpredicted mild stress (CUMS). The expression of serum BDNF was detected by enzyme-linked immunosor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 52 publications
7
40
0
Order By: Relevance
“…In addition, the social interaction test has revealed behavioral dysfunction [31]. These changes are accompanied by decreased hippocampal expression of BDNF [14]. In line with these previous findings, the present study found lower hippo- Total distance travelled in the OF test was significantly lower in the stress group than in the control group.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In addition, the social interaction test has revealed behavioral dysfunction [31]. These changes are accompanied by decreased hippocampal expression of BDNF [14]. In line with these previous findings, the present study found lower hippo- Total distance travelled in the OF test was significantly lower in the stress group than in the control group.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have indicated that BDNF expression in the salivary glands changes in response to stress [28,29]. Moreover, it is well established that the concentration of BDNF in blood decreases following stress in humans and various animal species [14,22]. The present findings indicate that social isolation stress also induces a reduction of BDNF in saliva and blood.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations